Cardiovascular disturbances in psycho-active substance and narcotic abuse - I. A. Nikiforov (Российский кардиологический журнал, 2007)
Psycho-active substance (PAS) abuse results in morpho-functional disturbances of various organs and systems. Cardiovascular pathology (CVP) is prevalent in visceropathy structure among PAS-dependent individuals. Based on literature data, an attempt to systematize specific and non-specific factors, affecting CVP pathogenesis in PAS abuse, is made.